Trocar- sharpened needles for image- guided prostate biopsy improve sample quality and performance: first clinical results - Simpfendörfer, Tobias; Kuru, Timur Hasan; Steinemann, Sarah; Gasch, Claudia; Roth, Wilfried; Hohenfellner, Markus; Hadaschik, Boris (Journal of endourology, 2014)
OBJECTIVE: To show the benefit of trocar-sharpened needles for image-guided prostate biopsy compared with standard bevelled needles in patients. MATERIALS AND METHODS: Twenty-four men underwent magnetic resonance imaging-targeted fusion-guided transperineal saturation prostate biopsy, each with half standard bevelled and half trocar-sharpened needles. All taken biopsies were scored (1=worse to 5=best) by one urologist for the following criteria. (1) Accuracy of matching between planned and performed biopsy. (2) Histologic quality of the sample. (3) Elegance, which is the easiness to take the biopsy in proper time, planned position, and best histologic quality. Afterward, the histologic sample quality was evaluated by a blinded pathologist. To show a possible training effect, blinded untrained junior residents performed biopsies in four men (103 cores). RESULTS: Overall, 600 single biopsies were analyzed. The trocar-sharpened needles demonstrated a significantly (p<0.05) better scoring for accuracy and elegance rated by the urologist. The histologic quality scored by the pathologist was superior. Moreover, significantly lower target errors with trocar-sharpened needles were achieved by untrained residents, but not by the experienced user. CONCLUSION: Using trocar-sharpened needles helps urologists to perform targeted prostate biopsy more elegantly and accurately. In addition, the histopathologic sample quality was superior, which may directly improve diagnostic certainty. There is an undeniable training effect in image-guided biopsy and unexperienced users can significantly reduce target errors with trocar-sharpened needles.
Gesehen am 11.11.2015